Mythen in deutschsprachigen Geschichtsschulbüchern Von Marathon bis zum Élysée-Vertrag - Bernhard, Roland (Georg-Eckert-Institut - Leibniz-Institut für Internationale Schulbuchforschung bei Vandehoek & Rupre, 2017)
Even in the 21st century, history textbooks are full of historical myths. This volume draws on cultural studies and history didactics to illuminate some of the myths contained in German Speking History Textbooks. The volume also reflects in depth upon the concept of 'myth' and proposes a definition that ties in to academic discourse on historical learning without denying the concept's roots in cultural studies.